PENGARUH KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA HOTEL NOVOTEL AIRPORT NGURAH RAI - Donna Meilia Indirawati; Ni Luh Sili Antari; Anak Agung Jemi Harta (Journal Research of Management, 2020)
This study aims to determine whether there is a simultaneous or partial influence between communication and work environment on employee performance at the Novotel Airport Ngurah Rai Hotel. The respondents of this study were 69 employees of Novotel Airport Ngurah Rai Hotel. The data analysis technique used is multiple linear regression analysis techniques. The T test is used to determine the effect of the independent variable on the dependent variable partially and the Determination test is used to determine the significant effect of the independent variable on the dependent variable simultaneously (simultaneously). Based on the analysis results it is known that the significance level of t is 0,000 which is smaller than 0.05 so that H1 and H2 are accepted. This means that communication and work environment have a significant effect on employee performance. And based on the test of determination that communication and work environment together significantly influence the performance of employees of the Novotel Airport Ngurah Rai Hotel. The results of the communication determination coefficient (X1) and work environment (X2) on employee performance (Y) in the Table shows a value of 0.671 or 67.1%. This means that the influence of communication and work environment variables of 67.1% while the remaining 32.9% is influenced by other factors outside the study. Based on the results of the study, it can be suggested that company leaders are expected to be more open in providing direction to subordinates, good and effective communication to continue to be established between superiors and subordinates or fellow employees in the company.Keywords: communication, work environment, employee performance.